2020
DOI: 10.1007/s11121-020-01145-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Educational Video in Maternity Wards to Prevent Self-Reported Shaking and Smothering during the First Week of Age: A Cluster Randomized Controlled Trial

Abstract: This study aimed to investigate whether watching an educational video on infant crying and the dangers of shaking and smothering within 1 week after delivery at maternity wards reduces self-reported shaking and smothering, at a 1-month health checkup. A cluster randomized controlled trial, stratified by area and hospital function, was employed in 45 obstetrics hospitals/clinics in Osaka Prefecture, Japan. In the intervention group, mothers watched an educational video on infant crying and the dangers of shakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The result showed that mothers’ knowledge of the peak of crying improved in the intervention group than in the control group (percentage of improvement: 31% vs. 13%, p = .026). The effectiveness of The Period of PURPLE Crying ® evaluated by Barr, Rivara, et al (2009) and Fujiwara, Isumi, Sampei, Miyazaki, et al (2020) also showed improved knowledge of mothers of newborns on normal crying patterns and dangers of shaking. However, in some studies, the same program did not improve parents’ knowledge of the dangers of shaking (Barr, Barr, et al, 2009; Fujiwara et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The result showed that mothers’ knowledge of the peak of crying improved in the intervention group than in the control group (percentage of improvement: 31% vs. 13%, p = .026). The effectiveness of The Period of PURPLE Crying ® evaluated by Barr, Rivara, et al (2009) and Fujiwara, Isumi, Sampei, Miyazaki, et al (2020) also showed improved knowledge of mothers of newborns on normal crying patterns and dangers of shaking. However, in some studies, the same program did not improve parents’ knowledge of the dangers of shaking (Barr, Barr, et al, 2009; Fujiwara et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…On the contrary, Barr, Barr, et al (2009) and Fujiwara et al (2012) reported an insignificant difference in the frequency of maternal behaviors, including taking a break in response to inconsolable crying, between the intervention and control groups. Similarly, parents who received AHT preventive programs involving strategies for responding to inconsolable crying may either use more self-talk to gain control over their emotions (Fujiwara, Isumi, Sampei, Yamada, et al, 2020; Morrill et al, 2015) or not (Barr, Barr, et al, 2009; Fujiwara, Isumi, Sampei, Miyazaki, et al, 2020). A synthesis of the effectiveness of AHT preventive parenting programs can provide a basis to optimize the design of future research and interventions to prevent AHT.…”
Section: Introductionmentioning
confidence: 99%
“…Example: A cluster-randomized trial in Japan examined the impact of a postpartum educational video on rates of selfreported shaking and smothering of newborns. 39 Forty-five obstetric units were randomized to receive or not receive the intervention. Analysis was performed by patient, comparing 2350 individuals in the intervention group to 2372 individuals in the no intervention group.…”
Section: Unit Of Analysismentioning
confidence: 99%
“…Example : A cluster-randomized trial in Japan examined the impact of a postpartum educational video on rates of self-reported shaking and smothering of newborns 39. Forty-five obstetric units were randomized to receive or not receive the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation